(untitled) (New Jersey, 2003)
The aim of the symposium was to focus on the new projects and new lines of research in nuclear physics that will be developed in the main laboratories and research centres during the next 10–20 years. The main emphasis was on the discussion (from both the experimental and theoretical viewpoints) of properties of nuclei under extreme conditions (at large mass numbers, at large isospin, at high temperature, and at nuclear densities far from equilibrium), by investigating nuclear collisions from low to relativistic energies. This proceedings volume is a collection of all the invited talks of the plenary sessions and oral contributions given by the speakers at the parallel sessions.
Keywords: Nuclear physics,Vật lý hạt nhân